Media policymaking and multistakeholder involvement: Matching audience, stakeholder and government expectations for public service media in Flanders. (April 2023) - Van den Bulck, Hilde; Raats, Tim
This contribution analyzes government, opposition, public service media, media stakeholders and audience views regarding the role and remit of public service media in the run-up to and their impact on the renewal of the 2021–2025 management contract between public broadcaster VRT and the Flemish Government. Results show that, despite a shifting media ecosystem and academics and government pushing for fundamental reform, audiences and most stakeholders' views stick to a centralised, broad and multiplatform public media institution. Moreover, they expect public service media to solve ever more media and societal issues (e.g. fake news) within a shrinking budget. The case illustrates how mature, evidence-based multistakeholderism pushes public service media to meet an increasingly challenging set of expectations, hampers both public service media and government to build a well-balanced, long-term vision of public service media's role and, instead, pushes them to pursue their own agenda. Lastly, an evidence-based process also suffers from issues of validity of the data.